The naming song - Berry, Jedediah (Tor, Tor Publishing Group, 2024)
"The Naming Song understands the fundamental magic of language, and breathes that magic onto every page." -Holly Black, #1 New York Times bestselling author There's nothing more dangerous than an unnamed thing When the words went away, the world changed. All meaning was lost, and every border fell. Monsters slipped from dreams to haunt the waking while ghosts wandered the land in futile reveries. Only with the rise of the committees of the named-Maps, Ghosts, Dreams, and Names-could the people stand against the terrors of the nameless wilds. They built borders around their world and within their minds, shackled ghosts and hunted monsters, and went to war against the unknown. For one unnamed courier of the Names Committee, the task of delivering new words preserves her place in a world that fears her. But after a series of monstrous attacks on the named, she is forced to flee her committee and seek her long-lost sister. Accompanied by a patchwork ghost, a fretful monster, and a nameless animal who prowls the shadows, her search for the truth of her past opens the door to a revolutionary future-for the words she carries will reshape the world. The Naming Song is a book of deep secrets and marvelous discoveries, strange adventures and dangerous truths. It's the story of a world locked in a battle over meaning. Most of all, it's the perfect fantasy for anyone who's ever dreamed of a stranger, freer, more magical world."--